Al-Sabouni method With the investigations of the sciences of the Qur’an (Journal of the College of Basic Education, 2022)
The science of interpretation is for the sake of Islamic sciences, and that is because it interprets the Noble Qur’an and studies the Noble Qur’an, which was revealed as a mercy to the worlds. It was revealed to bring people out of the darkness of ignorance and polytheism into the light of faith and monotheism. Therefore, Al-Sabouni was exposed, during his interpretation, to the subjects of the sciences of the Qur’an, which are the subjects related to the Book of God, may God bless him and grant him peace, in terms of its arrangement. and the reasons for its revelation, Makkah and Madinah, and its abrogator and abrogated to other investigations; Therefore, I decided to extract a chapter from the doctoral dissertation to publish it according to the applicable law in order to complete the doctoral study. The research is entitled “The Al-Sabouni Method” with the Qur’anic Sciences Investigation.